The analysis quality technique of the sequential recognition device of radar-tracking objects - A. S. Khramenkov; S. N. Yarmolik; A. S. Solonar (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Set of conditional probabilities of accepted decisions and average duration of classification procedure it is offered to characterize functioning quality of the sequential recognition device. The analytical calculation technique of quality indicators is developed. The technique basis is made by representation of interchannel differences multidimensional density of probabilities by the truncated number on orthogonal polynoms with optimum picked up weight function. At calculations the hypothesis about supervision continuation is considered to means of a numerical method of Monte-Carlo. Within preset values of the relation a signal-noise qualities demanded indicators are received. The received results have been confirmed by a method of statistical modelling.